2009
DOI: 10.1017/s0016756809006347
|View full text |Cite
|
Sign up to set email alerts
|

The onset of the North Atlantic Igneous Province in a rifting perspective

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 156 publications
1
38
0
Order By: Relevance
“…5; Larsen & Marcussen 1992;Hald & Tegner 2000). Throughout the North Atlantic Igneous Province it can be shown that there are two main periods of igneous activity, with ages of c. 62 -58 Ma and c. 57 -53 Ma, with detectable peaks at c. 60 Ma and at c. 55 Ma, respectively (Saunders et al 1997;Torsvik et al 2001;Jerram & Widdowson 2005;Hansen et al 2009;Brooks 2011, and references therein). These are often cited as relating to the impingement of the Iceland plume and the main phase of rifting and continental separation (Hansen et al 2009).…”
Section: Volcanic History Of East Greenland and The Jameson Land Basinmentioning
confidence: 99%
See 1 more Smart Citation
“…5; Larsen & Marcussen 1992;Hald & Tegner 2000). Throughout the North Atlantic Igneous Province it can be shown that there are two main periods of igneous activity, with ages of c. 62 -58 Ma and c. 57 -53 Ma, with detectable peaks at c. 60 Ma and at c. 55 Ma, respectively (Saunders et al 1997;Torsvik et al 2001;Jerram & Widdowson 2005;Hansen et al 2009;Brooks 2011, and references therein). These are often cited as relating to the impingement of the Iceland plume and the main phase of rifting and continental separation (Hansen et al 2009).…”
Section: Volcanic History Of East Greenland and The Jameson Land Basinmentioning
confidence: 99%
“…Saunders et al 1997;Hansen et al 2009;Jerram et al 2009;Brooks 2011;Nelson et al 2015). Along East Greenland this opening propagated northwards to the Norwegian-Greenland Sea and led to plate separation occurring during the Eocene (c. 55 Ma), and was accompanied by widespread igneous activity along 2000 km of the conjugate rifted margins (e.g.…”
Section: Volcanic History Of East Greenland and The Jameson Land Basinmentioning
confidence: 99%
“…62-53 Ma in response to the break-up of the North Atlantic and the impingement of a mantle plume at the base of the lithosphere (White and McKenzie, 1989;Saunders et al, 1997;Kent and Fitton, 2000;Emeleus and Bell, 2005;Storey et al, 2007;Hansen et al, 2009). Age relationships and radiometric dating suggest that the North Atlantic Igneous Province can be divided into two main phases of magmatic activity; one between ca.…”
Section: Sill Complexes In the North Atlantic Igneous Provincementioning
confidence: 99%
“…Voluminous sill complexes, dike swarms, volcanic centers, and extrusive igneous rocks, primarily of basaltic composition, were emplaced during these phases (~6.6 × 10 6 km 2 in total) and are located along two volcanic rifted margins; the conjugate east Greenland-northwest European and the west Greenland-Baffin Bay margins ( Fig. 2; Storey et al, 2007;Hansen et al, 2009). …”
Section: Sill Complexes In the North Atlantic Igneous Provincementioning
confidence: 99%
“…Continental break-up in the North Atlantic region between northwest Europe and East Greenland during the Palaeogene was accompanied by widespread volcanism associated with NAIP (e.g., Saunders et al, 1997;Hansen et al, 2009). Extensive lava fields, hydrovolcanic sequences, and subsurface intrusive complexes were emplaced on either side of the developing continental rift zone from the Late Paleocene to the Early Eocene followed by seafloor spreading.…”
Section: Study Areas North Atlantic Igneous Provincementioning
confidence: 99%